Penerapan Metode Belajar Tuntas Dalam Proses Pembelajaran - Andi Hamrina Bakri (Al-Ishlah: Jurnal Pendidikan Islam, 2020)
This paper describes the method of complete learning in the teaching and learning process as a form of solving the problem of low learning achievement of students associated with low absorption or not yet realized learning process skills that emphasize the active role of students focused on the problem of mastery learning "namely achievement of a minimum level of mastery that is set for each individual competency especially those who have learning difficulties. As educators, teachers should apply the method of thorough learning in every learning in order to motivate students so that the learning process is more meaningful, enjoyable, provides more appropriate quality of learning, assistance, and special attention for students who are slow to master competency standards or competencies basic, as well as achieving the expected learning achievement results.